2015
DOI: 10.1002/pmic.201400083
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species comparison of mammalian saliva using an LC-MALDI based proteomic approach

Abstract: Despite the importance of saliva in the regulation of oral cavity homeostasis, few studies have been conducted to quantitatively compare the saliva of different mammal species. Aiming to define a proteome signature of mammals' saliva, an in-depth SDS-PAGE-LC coupled to MS/MS (GeLC-MS/MS) approach was used to characterize the saliva from primates (human), carnivores (dog), glires (rat and rabbit), and ungulates (sheep, cattle, horse). Despite the high variability in the number of distinct proteins identified pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 61 publications
4
51
3
Order By: Relevance
“…By using mass spectrometry based proteomics, ten common proteins were found across seven mammals: carbonic anhydrase, albumin, polymeric immunoglobulin receptor, prolactin‐inducible protein, lactoperoxidase, glutathione‐S‐transferase, and keratins 1, 9, and 10. De Sousa‐Pereira et al., additionally reported that histatins and statherin were not found in dogs. In the present study, we set out to quantitatively analyze the protein composition of canine saliva for the first time in two differently sized breeds, Labrador retriever (large) and Beagles (medium), and to compare these with human saliva.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…By using mass spectrometry based proteomics, ten common proteins were found across seven mammals: carbonic anhydrase, albumin, polymeric immunoglobulin receptor, prolactin‐inducible protein, lactoperoxidase, glutathione‐S‐transferase, and keratins 1, 9, and 10. De Sousa‐Pereira et al., additionally reported that histatins and statherin were not found in dogs. In the present study, we set out to quantitatively analyze the protein composition of canine saliva for the first time in two differently sized breeds, Labrador retriever (large) and Beagles (medium), and to compare these with human saliva.…”
Section: Introductionmentioning
confidence: 96%
“…In depth analysis of the protein composition of canine saliva from three mixed breed individuals has been initiated by de Sousa‐Pereira et al. (2015) . Using qualitative gel electrophoresis to compare to other mammals, including humans, they demonstrated that canine saliva contained a smaller proportion of lower molecular weight proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Specialized diets have resulted in a number of physiological, biochemical, and morphological adaptations. In carnivores, several key diet-related physiological traits have been identified, including differences in digestive enzymes [7], shortened digestive tracts [8], changes in amino acid dietary requirements [9, 10], and alterations to taste bud sensitivities (including a heightened response to amino acids and a loss of response to many mono- and di-saccharides) [11, 12], to name a few. In addition to these characteristics, the morphology of cats is highly adapted to hunting and includes flexible bodies, fast reflexes, and strong muscular limbs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, saliva contains a smaller number and amount of endogenous proteins than milk, which may be advantageous for the purification of expressed foreign proteins. For example, the number of proteins detected in the saliva of humans and cattle is about 120013 and 90013 respectively, while the total protein concentration is 0.72 mg/ml14 and about 0.6–1.8 mg/ml15. More importantly, saliva can be collected repeatedly from various animals, including mouse, pig, cattle, sheep and goat by surgical or non-surgical methods121617181920.…”
mentioning
confidence: 99%